Topology - Munkres, James Raymond, 1930- (Harlow, Essex : Pearson Education, 2014)
For a senior undergraduate or first year graduate-level course in Introduction to Topology. Appropriate for a one-semester course on both general and algebraic topology or separate courses treating each topic separately. This text is designed to provide instructors with a convenient single text resource for bridging between general and algebraic topology courses. Two separate, distinct sections (one on general, point set topology, the other on algebraic topology) are each suitable for a one-semester course and are based around the same set of basic, core topics. Optional, independent topics and applications can be studied and developed in depth depending on course needs and preferences.
I. GENERAL TOPOLOGY. 1. Set Theory and Logic. 2. Topological Spaces and Continuous Functions. 3. Connectedness and Compactness. 4. Countability and Separation Axioms. 5. The Tychonoff Theorem. 6. Metrization Theorems and Paracompactness. 7. Complete Metric Spaces and Function Spaces. 8. Baire Spaces and Dimension Theory. II. ALGEBRAIC TOPOLOGY. 9. The Fundamental Group. 10. Separation Theorems in the Plane. 11. The Seifert-van Kampen Theorem. 12. Classification of Covering Spaces. 13. Classification of Surfaces.
Keywords: Topologie